Web-Based System Design And Implementation For Optimizing Pharmaceutical Logistics Management - Samdika Maulana Hafiz; Arridha Zikra Syah; Mustika Fitri Larasati (Brilliance: Research of Artificial Intelligence, 2026)
Medication logistics management plays a crucial role in supporting healthcare services, particularly in ensuring the availability of medicines at community health centers. However, the Sei Kepayang Barat Community Health Center still faces several challenges due to the use of manual systems in recording, monitoring, and reporting pharmaceutical data. These limitations often result in data inconsistencies, delays in information processing, and difficulties in tracking drug stock in real time. This study aims to design and implement a web-based pharmaceutical logistics information system to improve the effectiveness and efficiency of drug management processes. The research employed a qualitative approach through observation, interviews, and literature review to identify system requirements and existing problems. The system was developed using PHP and MySQL, with system design modeled through Unified Modeling Language (UML), flowcharts, and Entity Relationship Diagrams (ERD). The results indicate that the implemented system is capable of integrating key processes, including drug inventory management, procurement, distribution, and reporting. Furthermore, the system enables real-time monitoring of stock levels, reduces human error in data entry, and accelerates report generation. Overall, the web-based system contributes to improving the accuracy, transparency, and efficiency of pharmaceutical logistics management at the health center, thereby supporting better decision-making and enhancing the quality of healthcare services.